PENDIDIKAN ETIKA SEBAGAI SOLUSI ATAS KRISIS MORAL REMAJA SEKARANG - Marni Wati Benu (JIP: Jurnal Ilmu Pendidikan, 2025)
The moral crisis among today’s youth has become a serious concern in both educational and societal contexts. Phenomena such as a lack of respect for parents, increasing deviant behavior, and the erosion of values like honesty and responsibility indicate that education must go beyond cognitive development and emphasize ethics as the foundation of character. This article explores the role of ethical education as a practical solution to the moral challenges faced by adolescents. Using a descriptive qualitative approach through literature review and case analysis, this study highlights the importance of an integrative model involving schools, families, and communities. The findings show that when ethical values such as justice, empathy, honesty, and responsibility are instilled consistently, teenagers are more likely to develop positive attitudes toward themselves and others. Ethical education should not only be part of the curriculum but must also become a cultural practice in character formation. Therefore, cross-sector collaboration is essential to establish an ethical and impactful educational system that prepares youth to face moral challenges responsibly.